Graphitization as a Universal Tool to Tailor the Potential‐Dependent Capacitance of Carbon Supercapacitors. Issue 13 (8th May 2014) - Weingarth, Daniel; Zeiger, Marco; Jäckel, Nicolas; Aslan, Mesut; Feng, Guang; Presser, Volker
<x xml:space="preserve">Abstract</x> Most efforts to improve the energy density of supercapacitors are currently dedicated to optimized porosity or hybrid devices employing pseudocapacitive elements. Little attention has been given to the effects of the low charge carrier density of carbon on the total material capacitance. To study the effect of graphitization on the differential capacitance, carbon onion (also known as onion‐like carbon) supercapacitors are chosen. The increase in density of states (DOS) related to the low density of charge carriers in carbon materials is an important effect that leads to a substantial increase in capacitance as the electrode potential is increased. Using carbon onions as a model, it is shown that this phenomenon cannot be related only to geometric aspects but must be the result of varying graphitization. This provides a new tool to significantly improve carbon supercapacitor performance, in addition to having significant consequences for the modeling community where carbons usually are approximated to be ideal metallic conductors. Data on the structure, composition, and phase content of carbon onions are presented and the correlation between electrochemical performance and electrical resistance and graphitization is shown. Highly graphitic carbons show a stronger degree of electrochemical doping, making them very attractive for enhancing the capacitance.